A STUDY OF INDIGENOUS TOURISM PRODUCT DEVELOPMENT CASE STUDY: THE BADUY, SOUTH BANTEN, WEST JAVA - Komang Trisna Pratiwi Arcana; Kadek Wiweka (Jurnal Ilmiah Hospitality Management, 2016)
Tourism is believed to deliver both positive and negative impact. This phenomenon occurs in one of the indigenous villages of Baduy tribes, where the village is â€œisolatedâ€ from modern development of urban areas. This study used several variables that written in an interview manuscript, created based on some literatures about indigenous tourism product development; tourism impact perspective, and tourists motivation. The data have been collected are then combined using two approaches both quantitative and qualitative or known as a â€œmulti-methodâ€. Data obtained through questionnaires was presented by the chart (in the form of quantitative), and described into a sentence. While the interview data will be put into the interview manuscript, which subsequently combined with the results of questionnaires and observations. This study found that the Baduy village has a variety of potential that can be packaged as a tourism product, such as: have the cultural and natural attractions that still maintained its authenticity, a location away from the frenetic urban communities began receiving tourism activities. Surveys in this study also found that, variables such as cultural tourism products, local communities and nature is considered very important and can attract urban travelers. This is evidenced by the results of the questionnaire, where tourists visiting Baduy village, dominated by teenagers who mostly still a student and travel in groups. While the motivation of their visit was mostly to leisure in a way out of the urban routine. The effects of tourism activities on the socio-cultural environment, the economy and the environment have not seen significantly. Advice and feedback to the Baduy Tourism Village are to strengthen the rules and regulations village environment so as to anticipate the changes that can occur if the pressure changes constantly occur tourism at the Tourism Village Baduy. In addition, increase the role of local communities should also be improved by involving the community in organizations such as the travel conscious group.